Digital Transformation: Opportunity or Threat to Employability? - Rojas-Romero, Rolando; Valdés-González, Héctor; Reyes-Bozo, Lorenzo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper presents a critical analysis of the Digital Transformation’s (DT) effects on employability within organizations in Chile, providing an action reference framework for competitiveness in the field. To achieve this, a qualitative approach to the opinions of a convenience sample of executives and leaders was employed, based on semi-structured interviews, to understand how to address this type of transformation. The analysis indicates that, having long-term policies for the development of new skills in their collaborators is a critical success factor. These policies are summarized in three stages, through a reference framework for the generation of specific actions in pursuit of the development of a successful DT process. DT fosters a cultural change in the entities to generate capacities that allow them to anticipate the evolution of the market and adapt quickly to it, for which it is fundamental to promote the training of new technical and behavioral skills in collaborators, in addition to encouraging them to self-train.